Collagen Binding Assay for von Willebrand Factor (VWF:CBA): Detection of von Willebrands Disease (VWD), and Discrimination of VWD Subtypes, Depends on Collagen Source - Favaloro, Emmanuel J. (Thrombosis and Haemostasis, 2000)
A large number of different collagen preparations [n = 21] have been assessed for their ability to both detect von Willebrands Disease (VWD), and discriminate different VWD subtypes. Collagen preparations were tested at a range of concentrations and included: Type I, III and IV, and various mixtures of these, as aqueous supplied preparations and/or reconstituted from bulk lyophilised stock. Tissue sources for collagens ranged from human placenta to calf skin to equine tendon. Three of the collagen preparations tested did not support von Willebrand factor (VWF) binding in an ELISA process (therefore unable to detect VWD). The ability of the remaining preparations to detect VWF was variable, as was their ability to discriminate VWD subtypes. Detection of VWF and discrimination of VWD subtypes was not mutually inclusive. Thus, some collagen preparations provided excellent detection systems for VWF, but comparatively poorer discrimination of Type 2 VWD, while others provided good to acceptable detection and discrimination. Subtype discrimination was also dependent on the collagen concentration, and some batch to batch variation was evident with some preparations (particularly Type I collagens). Overall, best discrimination was typically achieved with Type I/III collagen mixtures, or Type III collagen preparations (where effectiveness was highly dependent on concentration). Good discrimination was also achieved with a commercial Type III collagen based VWF:CBA kit method. Results of the various ‘VWF:CBA assays’ are also compared with those using the Ristocetin Cofactor (VWF:RCof) assay (by platelet agglutination) and that using a commercial ‘VWF:RCof-alternative/ activity’ ELISA procedure. These latter methodologies tended to be less sensitive to VWF-discordance when compared to that detected by the majority of the VWF:CBA procedures.Abbreviations: FVIII:C Factor VIII: coagulant (assay); HMW High Molecular Weight [VWF]; PNP Pooled Normal Plasma; RIPA Ristocetin induced platelet aggregation procedure; VWD von Willebrands disease; VWF von Willebrand Factor; VWF:Ag von Willebrand Factor Antigen (assay); VWF: CBA Collagen Binding [Activity] Assay for VWF; VWF:RCof Ristocetin Cofactor Assay for VWF
Keywords: von Willebrand factor; VWF; von Willebrands disease; VWD; collagen binding assay; collagen; VWF:CBA